Monster hunt [videorecording (DVD)] - Hui, Raman; Bai, Baihe, 1984-; Jing, Boran, 1989-; Jiang, Wu, 1967- (FilmRise : Fisher Klingenstein Ventures, LLC, 2016)
As the infant child of the monster queen and a human father, Wuba's mere existence causes humans and monsters to each plot to kidnap the baby, a task that proves to be no easy feat.